Decisions : an engineering and management perspective - Gaynor, Gerard H. (Hoboken, New Jersey : IEEE Press/Wiley, 2015)
DECISIONS examines the issues required to stimulate new thinking for improving the decision-making process and achieve higher project success rates for all managerial levels. This book considers what it takes to convert the macro decision into a positive outcome; to resolve the gap that exists between the macro and subsidiary decisions; to understand why so many decisions fail to meet expectations; to direct the mindset of the engineering community to focus on its relation to other organizational units; to perform diligently the up-front work required to meet objectives; to stop squandering valuable talent and resources; to urge engineers and other discipline professionals to take a more business-oriented approach in participating in the organization's decision-making process; lastly, to not only recognize the importance of and the role of communication in all decision-making processes, but to initiate appropriate communication processes. The author addresses these topics which encompass macro and micro decisions by: . Presenting critical decisions that need to be addressed in conjunction with preparations for making the macro decision . Including simple illustrations and case studies to aid the process of decision-making . Highlighting research related to problems associated with meeting requirements, schedule, and cost . Presenting a share of factors, e.g. global economy, global participation, and global access to human and physical resources that add layers of complexity and are too often neglected The author tackles the challenges changing the mindset of engineering and its managers, and convincing executive level management to pursue to the up-front work with greater diligence prior to making commitments.
Promotions and Appointments 124 -- Selecting Team Members 126 -- Selecting the Right People 130 -- Assigning Work 131 -- Transitioning From Specialist to Manager 132 -- Salary Schedules 134 -- Continuing Education 134 -- Building a Succession Competence 136 -- Key Points 137 -- Notes 138 -- 7 DEVELOPING DECISION-MAKING COMPETENCIES 139 -- Decision Dilemmas 140 -- Learning to Make Decisions 144 -- Educating for Decision-Making 147 -- Dealing with Ambiguity 153 -- Executing the Deliverables 156 -- Key Points 162 -- Notes 163 -- 8 IBM ROCHESTER, MINNESOTA: THE SILVERLAKE PROJECT 165 -- Birth of IBMR Minnesota 166 -- Project Fort Knox 167 -- IBMR Faces Market Challenges 168 -- New Directions for IBM Rochester 168 -- Furey Asks the Hard Questions 169 -- Ambitious Goals 173 -- Market Launch 176 -- Lessons Learned 177 -- Key Points 184 -- Notes 185 -- 9 BOEING AND THE 787 DREAMLINER 187 -- Dreamliner Scope and Expectations 188 -- Boeing-The Enterprise 189 -- The 787 Dreamliner Challenges 192 -- Commentary 198 -- Key Points 213 -- Notes 216 -- 10 COMMUNICATION IN DECISION-MAKING 219 -- New-to-the-Market Product 221 -- What is Communication? 226 -- Types of Communication 228 -- Organizational Context 231 -- Barriers to Effective Communication 234 -- Ethical Issues in Communication 253 -- Eliminating the Communication Barriers 255 -- Key Points 258 -- Notes 259 -- 11 EVALUATING DECISION-MAKING PERFORMANCE 261 -- People 262 -- Purposes 264 -- Processes 265 -- Strategic Thinking 266 -- Culture 267 -- Products and Services 268 -- Resources 270 -- Leadership 275 -- Innovation and Entrepreneurship 276 -- Organizational Readiness 278 -- Policies and Procedures 279 -- Employee Benefits 279 -- Downsizing 280 -- Going Global 281 -- Government Regulations 282 -- Offshore Operations 282 -- Integrating Organizational Units 283 -- General Governance Issues 284 -- Key Points 289 -- Notes 292 -- Index 293.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Decision making; Problem solving; Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Decision making; Management; Problem solving; Electronic books; Electronic books